Niche partitioning facilitates coexistence of three apex predators in the Lapchi Valley, Central Himalaya, Nepal - Narayan Prasad Koju; Babita Maharjan; Meghajan Budha; Ashim Thapamagar; Nishan Pokhrel; Miriam Lee; Laxman Khanal; Paul Buzzard; Xuelong Jiang; Randall C. Kyes (PLoS ONE, 2026)
Large carnivores increasingly coexist in human-modified mountain landscapes, yet empirical evidence on how multiple apex predators partition space, time, and resources to reduce competition remains limited, particularly in the Central Himalaya, Nepal. Understanding these mechanisms is critical for predicting interspecific interactions and informing conservation practices in resource-limited alpine ecosystems. This study explored the ecological interactions, competitive dynamics, and coexistence strategies of sympatric snow leopards ( Panthera uncia ), leopards ( Panthera pardus ), and Himalayan wolves ( Canis lupus chanco ) in the Lapchi Valley, Central Himalaya, Nepal. We examined spatial distribution, temporal activity patterns, and dietary overlap among these apex predators using a combination of camera trapping, scat-based DNA analysis, and micro-histological diet assessment. The results showed a complete (100%) spatial overlap between the snow leopards and wolves’ ranges. All three predators exhibited predominantly nocturnal activity with strong temporal overlap (0.78). Dietary analyses showed a clear trophic segregation: snow leopards relied mainly on wild ungulates, leopards consumed synanthropic prey, while wolves consumed a mixed diet combining wild and domestic prey. Pianka’s index indicated high dietary overlap between snow leopards and wolves (0.77), but remarkably low overlap of these predators with leopards. The multidimensional niche partitioning appears to reduce direct competition among predators. These findings highlight the role of behavioral flexibility, spatial segregation, and prey selection in promoting the coexistence of predators. Conservation strategies must prioritize sustaining wild prey populations, mitigating livestock depredation, and addressing climate-driven habitat shifts that may intensify interspecific competition.